The Strategies for Cultivating an Arabic Language Environment - Nabilah, Aisyah Hanun; Rosikh, Fahrur; Kholish, Nurhafizah Mashitha (Funun Arabiyyah: Journal of Arabic Education and Literature, 2025)
This study aims to describe the strategy of forming an effective Arabic language environment in Islamic boarding schools. Arabic as the main language in Islamic literature requires a learning approach that is not only theoretical, but also practical through the creation of a linguistic environment. This study uses a qualitative approach with a descriptive method. Data collection was carried out through in-depth interviews, participatory observations, and documentation. The research informants consisted of pesantren caregivers, Arabic teachers, and students. The results of the study show that the strategy of forming an Arabic environment in Islamic boarding schools is carried out through various programs, such as the habit of speaking Arabic in daily communication, muhadatsah (conversation) training, speech competitions, and the preparation of a structured schedule for the use of Arabic. The main supporting factors include support from pesantren leaders, commitment of teaching staff, and student discipline. The inhibiting factors include limited learning facilities, lack of professional teaching staff, and differences in the background of students' ability in Arabic. This study concludes that the success of the strategy for the formation of an Arabic language environment is highly dependent on the continuity of programs, institutional support, and a conducive pesantren culture.